2004
DOI: 10.1258/1357633042602017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and categorization of acral melanocytic lesions using teledermoscopy

Abstract: We performed a multicentre study to test the validity of teledermoscopy for diagnosing acral melanoma and to evaluate inter-observer agreement on the classification of acral melanocytic lesions. Dermoscopic images of 77 acral melanocytic lesions (71 common melanocytic naevi and 6 melanomas) were sent by email to 11 dermatologists with different degrees of experience in dermoscopy. The observers analysed the images on a computer monitor to diagnose acral melanoma or atypical lesions and to categorize all lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(28 reference statements)
2
23
0
3
Order By: Relevance
“…With 66 acral melanomas this is the largest series on dermoscopy of acral melanoma in a predominantly Caucasian population to date [13,14,15,16]. Eight lesions (3 melanomas) were from Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…With 66 acral melanomas this is the largest series on dermoscopy of acral melanoma in a predominantly Caucasian population to date [13,14,15,16]. Eight lesions (3 melanomas) were from Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…All studies used a repeated measures study design with the exception of one randomized controlled trial. 11 Based on location, most of the studies were conducted in the United States (n = 14), [3][4][5][6]22,24,25,33,35,37,[41][42][43]45 followed by the United Kingdom (n = 9), 11,12,15,18,29,30,32,38,44 Italy (n = 6), 7,8,20,21,36,39 Spain (n = 4), 9,10,13,17 Australia/New Zealand (n = 3), 14,31,40 Turkey (n = 2), 16,19 and one study each from Germany, 23 Netherlands, 24 Pakistan, 27 Brazil, 28 and Switzerland. 34 Patient and skin condition characteristics.…”
Section: Summary Of Studies For Key Questions 1 Andmentioning
confidence: 99%
“…Fourteen studies included subjects younger than 18 years. 3,6,8,13,14,16,17,20,21,29,30,35,36,39 In 22 studies reporting gender, most of the subjects were male (57% overall, range 29%-98%). Only 6 studies, all conducted in the United States, reported racial or ethnic characteristics.…”
Section: Summary Of Studies For Key Questions 1 Andmentioning
confidence: 99%
“…In a smaller study by the same investigators of 13 lesions (pigmentation status not reported), aggregated diagnostic accuracy was 80% and 92% for two different clinic dermatologists and 85% for two different teledermatologists using macro images only. 11 Several studies have specifically evaluated pigmented lesions with teledermatology and/or teledermatoscopy [23][24][25][26][27][28][29] but only one, to our knowledge, specifically reported results for nonpigmented lesions. Fabbrocini and colleagues 30 evaluated 44 ''difficult pink lesions'' and reported a ''correct diagnosis'' rate of 66% for clinicians versus 52% for teledermatologists using teledermatoscopy with immersion oil.…”
Section: Main Study Findingsmentioning
confidence: 99%